BOAT LIFT NET FISHING GEAR WHICH OPERATED AT BANTEN BAY WATERS AND ITS DEVELOPMENT STRATEGY - Iskandar, Mokhamad Dahri; Wassahua, Zainal; Muqsit, Ali; Warsini, Sati; Tahapary, Nona; Siregar, Resmi (Politeknik Kelautan dan Perikanan Dumai, 2023)
Bagan congkel is one of fishing gear which mostly used by fishermen in National Fishing Port of Karangantu, Banten. Bagan congkel has various size and specification in Indonesia. Characteristic of fishing ground and fish catch was also different at different area in Indonesia. Therefore, to develop bagan congkel in Teluk Banten waters need a good and systematics strategy. The objective of this experiment was to describe bagan congkel fishing gear and determine business development strategy of bagan congkel. Business development strategy was cariied out using SWOT Analyses (Strengths, Waeknesses, Opportunities, Threats). Result of research indicated that bagan congkel consist of boat which used to find fishing ground, net and lamp. There are 9 strategies to develop boat lift net i.e market enlargement, fishing optimalization, fish bottom price determination, fishing ground zonation each fishing gear, limitation of fishing fleet and fishing effort, selective fishing gear modification, capital loan for fishermen and combination of production factors to reach the efficiency.